Does public education expenditure cause economic growth? Comparison of developed and developing countries - Alvina Sabah Idrees; Muhammad Wasif Siddiqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The purpose of this paper is to examine the long-run relationship between public education expenditures and economic growth. The social benefits of education exceed its private benefits. Therefore, education is considered a merit good; if not supplied by the public sector, private production is undersupplied. The study has employed heterogeneous panel data analysis. Panel unit root tests are applied for checking stationarity. The single-equation approach of panel cointegration (Kao, 1999); Pedroni's Residual-Based Panel Cointegration Test (1997; 1999) is applied to determine the existence of long-run relationship between public education expenditures and gross domestic production. Lastly, panel fully modified ordinary least square results indicate that the impact of public education expenditures on economic growth is greater in the case of developing countries as compare to the developed countries, which verified the "catching-up effect" in developing countries.
Keywords: 330; Economic growth; education expenditure; fully modified ordinary least square; human capital